The Perception on online shopping among Muamalat students in UiTM Puncak Alam / Ahmadul Hadi Zammari. - Zammari, Ahmadul Hadi (2019)
This study is to know the perception on online shopping among students of the 5th semester of the diploma Muamalat Academic Contemporary Islamic Study (ACIS) UiTM Puncak Alam. This study only for the student IC 110 5A. The total number of students involved is 36 people(population). The method used qualitative to achieve objectives. This study also uses quantitative through the circulation of the questionnaire set among students in the semester 5. The result showed that the Muamalat students Acis, in UiTM Puncak Alam have a good perception about online shopping.